Risks and management of alien freshwater crayfish species in the Rhine-Meuse river district - Lemmers, Pim; Collas, Frank; Gylstra, Ronald; Crombaghs, Ben; van der Velde, Gerard; Leuven, Rob (Management of biological invasions, 2021)
Since the 1950s, nine alien crayfish species have been introduced in the Rhine-Meuse river delta. Seven species originate from North America, one from Southeast Europe and one from East Europe/Asia. Currently, at least seven species have well-established populations. Five species are listed as invasive alien species (IAS) of European Union (EU) concern (i.e. Faxonius limosus, Faxonius virilis, Pacifastacus leniusculus, Procambarus clarkii and Procambarus virginalis). All crayfish species of EU concern are subject to restrictions on keeping, transportation, importing, selling and breeding. Member States are required to take action on pathways of unintentional introduction, to perform measures for early detection and rapid eradication of these species, and to manage species that are already widely spread. The impact of these IAS on biodiversity and functioning of ecosystems mainly results from transmission of the crayfish plague pathogen Aphanomyces astaci, predation on native fauna, and fragmentation and consumption of aquatic plants. Moreover, burrowing activities of some IAS cause bank instability, increase risk of dike breaches in peatland areas and enhance sedimentation rates in ditches and canals. First-line risk assessments for the Rhine-Meuse river district with the Harmonia+ scheme shows that seven crayfish species have a high risk of impact on biodiversity, water safety and ecological status of water bodies. Four species have already established populations in this area of concern. The risk of spread via interconnected rivers, canals and small watercourses is high for all species of North American origin. Eradication of alien crayfish populations in an extensive and open network of interconnected watercourses is not feasible. Six management strategies for control of alien crayfish species were formulated. These strategies were assessed using various criteria for cost-effectivity and subsequently prioritized using an unweighted Multi Criteria Analysis. Feasible strategies for population control of invasive crayfish species combine a) measures for enhancing robustness and resilience of ecosystems, and b) crayfish trapping by commercial fishermen, water authorities and well-informed citizens.